Entrepreneurs’ intention to invest in current business: an empirical study of Malaysian SME entrepreneurs - Mohd Hizam Hanafiah,; Sh. Usman Yousaf,; Noor Azuan Hashim, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Entrepreneurs’ intention to invest in their current businesses may play an important role in determining future sustainability, survival and growth of these businesses. Using a theoretical framework based on entrepreneurs’ goals attainment theory (EGAT), this study evaluated the relationship between entrepreneurs’ personal goal attainment and their intention to invest. The study employed a positivist methodological framework and gathered primary data from 285 Malaysian entrepreneurs through self-administered survey questionnaires. Regression analyses showed that entrepreneurs’ attainment of economic and intrinsic reward goals had significant positive relationships with their intention to invest. Desire for independence was considered as an important motivation for entrepreneurship. However, it was found that attainment of independence goals had no significant influence on entrepreneurs’ intention to invest. Further, it was also found that more educated entrepreneurs had stronger intention to invest in their current businesses.